Role of Vasopressin Receptor 2 and 3 in ACTH-Secreting Tumors and their Potential Therapeutic Implications - Yang, Jia; Yang, Yehong; Wang, Yongfei; Zhang, Shuo; Cheng, Haixia; Wang, Shuyang; Ge, Liang; Li, Yiming; Ye, Hongying (Experimental and Clinical Endocrinology & Diabetes, 2020)
Purpose We investigated the expression of vasopressin receptor 2 and 3 on corticotrophin tumor cells, their role in regulating ACTH secretion, and their potential therapeutic implications.Methods We retrospectively assessed 52 hospitalized patients with pathologically confirmed ACTH-secreting tumors. The expression of vasopressin receptor 2 and 3 was explored via qualitative and quantitative immunohistochemistry analyses. The role of vasopressin receptors in regulating ACTH secretion was further studied in the AtT-20 cell line.Results Among 50 cases of pituitary corticotrophin adenoma, 31 were vasopressin receptor 2 positive, 38 were vasopressin receptor 3 positive, and 24 were both vasopressin receptor 2 and 3 positive. Two patients with ectopic ACTH syndrome were vasopressin receptor 3 positive, and one was also vasopressin receptor 2 positive. In 12 patients who underwent bilateral inferior petrosal sinus sampling before surgery, the central ACTH increment ratio after desmopressin stimulation was correlated with vasopressin receptor 2 but not with vasopressin receptor 3 staining intensity. In an in vitro study, the expression of both vasopressin receptor 2 and 3 on AtT-20 cells was confirmed. The vasopressin receptor 2 antagonist Tolvaptan inhibited desmopressin-induced ACTH secretion in a dose-dependent manner.Conclusions Both vasopressin receptor 2 and 3 are expressed in ACTH-secreting tumors. Vasopressin receptor 2 rather than vasopressin receptor 3 is the primary receptor that seems to mediate the ACTH response in corticotrophin tumors. A vasopressin receptor 2 antagonist can inhibit ACTH secretion induced by desmopressin in AtT-20 cells.
Keywords: pituitary; Cushing's disease; ectopic ACTH syndrome; vasopressin receptor 2 antagonist